The Consumption of Synbiotic Bread Containing Lactobacillus sporogenes and Inulin Affects Nitric Oxide and Malondialdehyde in Patients with Type 2 Diabetes Mellitus: Randomized, Double-Blind, Placebo-Controlled Trial. (17th August 2016) - Bahmani, Fereashteh; Tajadadi-Ebrahimi, Maryam; Kolahdooz, Fariba; Mazouchi, Marjan; Hadaegh, Haleh; Jamal, Atefeh-Sadat; Mazroii, Navid; Asemi, Shiva; Asemi, Zatolla
Abstract : Objectives: To our knowledge, no reports are available indicating the effects of synbiotic bread consumption on nitric oxide (NO), biomarkers of oxidative stress, and liver enzymes among patients with type 2 diabetes mellitus (T2DM). This study was performed to determine the effects of the daily consumption of synbiotic bread on NO, biomarkers of oxidative stress, and liver enzymes in patients with T2DM. Methods: This randomized, double-blind, placebo-controlled trial was performed among 81 patients with diabetes, aged 35–70 years old. After a 2-week run-in period, patients were randomly divided into 3 groups: group A ( n = 27) received synbiotic bread containing viable and the heat-resistant probiotic Lactobacillus sporogenes (1 × 10 8 CFU) and 0.07 g inulin per 1 g, group B ( n = 27) received probiotic bread containing Lactobacillus sporogenes (1 × 10 8 CFU), and group C ( n = 27) received control bread for 8 weeks. Patients were asked to consume the synbiotic, probiotic, or control breads 3 times a day in 40 g packages for a total of 120 g/day. Fasting blood samples were taken at baseline and after an 8-week intervention for quantificationof related markers. Results: After 8 weeks, the consumption of synbiotic bread compared to the probiotic and control breads resulted in a significant rise in plasma NO (40.6 ± 34.4 vs 18.5 ± 36.2 and −0.8 ± 24.5 µmol/L, respectively, p < 0.001) and a significant reduction in malondialdehyde (MDA) levels (−0.7 ± 0.7 vs 0.6 ± 1.7 and 0.5 ± 1.5 µmol/L, respectively, p = 0.001). We did not find any significant effect of the synbiotic bread consumption on plasma total antioxidant capacity (TAC), plasma glutathione (GSH), catalase, serum liver enzymes, calcium, iron, magnesium levels, and blood pressure compared to the probiotic and control breads. Conclusion: In conclusion, consumption of the synbiotic bread for 8 weeks among patients with T2DM had beneficial effects on plasma NO and MDA levels; however, it did not affect plasma TAC, GSH, catalase levels, serum liver enzymes, calcium, iron, magnesium levels, and blood pressure.